Social information processing problems related to reactive and proactive aggression of adolescents in residential treatment. (February 2016) - Oostermeijer, S.; Nieuwenhuijzen, M.; van de Ven, P.M.; Popma, A.; Jansen, L.M.C.
Abstract: Adolescents in residential treatment predominantly show externalizing problems. To provide more tailored treatments, gaining knowledge on underlying processes is important. Aggression is often subdivided in defensive/reactive, and instrumental/proactive aggression. The social information processing (SIP) model assumes that reactive aggression involves early SIP, whereas proactive aggression involves late SIP. This study investigated SIP steps in relation to reactive and proactive aggression of adolescents in residential treatment. In total 81 adolescents were included in the main analyses. A social information processing task using video-vignettes measured sequential SIP steps. Both zero-order and partial correlations with reactive and proactive aggression were investigated. Early SIP related to both subtypes of aggression, recognizing problems was negatively related to proactive aggression. The late SIP steps generating antisocial goals and responses were related to both aggression subtypes. Feeling competent and positive evaluation related to reactive aggression, while overseeing consequences related to proactive aggression. Partial correlations were non-significant. Post-hoc analysis for males and females separately showed differences in relationships between aggression measures and SIP. The current study indicates that both subtypes of aggression are related to early and late SIP steps. However, discrepancies are present which could potentially provide specific targets for treatment. Highlights: Reactive/proactive aggression and the relation with social information processing is studied. Both reactive and proactive aggression related to early and late social information processing. Differences between males and females were found. Discrepancies are present and could potentially provide specific treatment targets.